The Influence of Using “Hello Talk” Smartphone Application on Android Platform in Improving Students’ Learning Outcomes in Listening Class - Haris Mayekti, Meilina; Ade Chrystanty Yudha Bestary (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
This study aims to determine the influence of using the Hello Talk application based on the Android smartphone platform on improving the learning outcomes of English Education students at UNU Purwokerto in the listening class. The media used in the Hello Talk application are chat and voice-to-text features to assist in learning listening. Conversations which is used in application could be conducted personally or in group. Hello Talk plays a significant role in literacy culture in improving listening learning outcomes for the younger generation. This study implemented Hello Talk as a learning media in the listening class. Students engaged in listening learning using the Hello Talk application. The researcher used an experimnetal research design, where this method was applied to two groups: experimental group and control group. The population in this study consisted of 24 students, and all of them are used as samples. There were twelve students in the control group and twelve students also in the experimental group. The t-test value was higher than t-table. The result of t-test formula was 0.1 and the t-table is 0.05. Overall, Hello Talk application can give good influence for learning listening.